Water Sorption and Diffusion in (Reduced) Graphene Oxide‐Alginate Biopolymer Nanocomposites. Issue 9 (14th June 2016) - Vilcinskas, Karolis; Zlopasa, Jure; Jansen, Kaspar M. B.; Mulder, Fokko M.; Picken, Stephen J.; Koper, Ger J. M.
Abstract : (Reduced) graphene oxide‐alginate biopolymer nanocomposites show potential for water barrier coating applications. Depending on the composition, the composites can significantly reduce water sorption and mobility of water molecules. Interactions between filler and polymer chains reduce available sorption sites for water molecules. Also, the presence of filler creates obstacles for diffusing species, thus endowing composites with improved barrier properties. Abstract : The water sorption and diffusion in (reduced) graphene oxide‐alginate composites of various compositions is analyzed. Water sorption of sodium alginate can be significantly reduced by the inclusion of graphene oxide sheets due to the formation of an extensive hydrogen bonding network between oxygenated groups. Crosslinking alginate with divalent metal ions and the presence of reduced graphene oxide can further improve the swelling resistance due to the strong interactions between metal ions, alginate, and filler sheets. Depending on conditions and composition, the overall water barrier properties of alginate composites improve upon (reduced) graphene oxide filling, making them attractive for moisture barrier coating applications. Water sorption kinetics in all alginate composites indicate a non‐Fickian diffusion process that can be accurately described by the Variable Surface Concentration model. In addition, the water barrier properties of sodium alginate‐graphene oxide composites can be adequately predicted using a simple model that takes the orientational order of filler sheets and their effective aspect ratio into account.